حديث أبي لبابة في النهي عن قتل جنان البيوت: دراسة نقدية - الكساسبة، فيصل مفضي عثمان; المعايطة، عطا الله بخيت حماد (جامعة مؤتة, 2017)
This research represents a critical study for the saying. These houses are inhabited, so if you see anything from it you must ask these inhabitants to leave it three times. The researcher took the critics that are towards this Hadith and he showed the scientific value for these critics and he showed the meaning of the Demons (Jinan) and that we should alert them and not to kill them as it was shown in many texts with showing the meaning of calling these Demons to leave these houses as shown in these sayings.
يمثل هذا البحث دراسة نقدية لحديث: (إن لهذه البيوت عوامر، فإذا رأيتم شيئا منها فحرجوا عليها ثلاثا) تناول فيه الباحث الانتقادات الموجهة للحديث، وبين القيمة العلمية لهذه الانتقادات، ومن ثم توضيح المقصود بالجنان التي جاءت النصوص تنهى عن قتلها وتأمر بإنذارها، مع بيان المراد بالتحريج الوارد في هذه الأحاديث وكيف يكون؟
Keywords: الأحاديث النبوية -- نقد الحديث -- عوامر البيوت -- جن البيوت